Green Economy as a New Pathway to Development (and Cohesion)? Place Evidence Analysis in the North-Eastern Italy: First Findings of an Ongoing Research Project - Francesca Krasna; Giuseppe Borruso; Giovanni Mauro; Gian Pietro Zaccomer (Bollettino della Società Geografica Italiana, 2020)
This paper shows the first findings of an ongoing research project on “Territorial Impact Assessment of the Italian regions territorial cohesion. Place based evidence model for the policy evaluation towards the development of green economy in inner and metropolitan peripheries”, coordinated by Maria Prezioso (Tor Vergata University, Rome) as Principal Investigator. We hereby present the results of the first two years of investigation carried out by the Research Unit number 8, located in Trieste.